THE EFFECT OF PACKAGING ON THE SHELF LIFE OF STEAMED BROWNIES - Dhanang Puspita (Science Technology and Management Journal, 2026)
This study investigated the effect of three different packaging types, namely thin plastic mica, ziplock bags, and standing pouches, on the quality and shelf life of steamed chocolate brownies during 7 days of storage at room temperature (with moisture content measured for the first 4 days). The observed parameters included moisture content, texture, and organoleptic properties. The results showed that the packaging type significantly influenced the rate of moisture loss and textural changes. Thin mica packaging caused a rapid decrease in moisture content (from 30.0% to 16.7%) and significant texture hardening, leading to premature quality deterioration. Ziplock bags effectively retained moisture but triggered mold growth after day 5 due to high water activity. Standing pouches demonstrated optimal performance with controlled moisture loss (from 31.4% to 24.0%) and gradual texture changes, offering the best balance for extending shelf life.